POLA KOMUNIKASI GURU DENGAN SISWA TUNARUNGU DALAM BERINTERAKSI DI SEKOLAH LUAR BIASA YAYASAN AMAL BHAKTI SICINCIN KABUPATEN PADANG PARIAMAN - Putri, Melia Rahma; Awza, Rusmadi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
The hearing impaired are those who experience disturbances in their hearing organs, resulting in an inability to hear, ranging from mild to very severe levels, classified as deaf and hard of hearing. SLB Yayasan Amal Bhakti is an educational institution specifically designed to provide education to children with special needs, including hearing-impaired children, to train their speaking and communication skills. Therefore, teachers need to use appropriate communication patterns and instructional communication methods suitable to the students' conditions. The purpose of this study is to analyze the communication patterns that occur between teachers and hearing-impaired students and to analyze the forms of teaching methods between teachers and hearing-impaired students at SLB Yayasan Amal Bhakti Sicincin, Padang Pariaman Regency. This research uses descriptive qualitative research methods and uses George Harbert Mead's Symbolic Interaction theory. The informants in this study were six people, including the school principal, one teacher who taught deaf students, two deaf students and two guardians of deaf students who were selected based on certain requirements using a purposive sampling technique. Data collection techniques are carried out through observation, interviews and documentation. The data analysis technique uses interactive analysis according to Miles and Huberman, namely data collection, data reduction, data presentation and drawing conclusions. The data validity techniques used are extended participation and triangulation. The results of the study show that there are three communication patterns used by teachers at SLB Yayasan Amal Bhakti to facilitate the learning process, communication, and interaction with hearing-impaired students: one-way communication, two-way communication, and multi-way communication patterns. There are four teaching methods used by teachers in the learning process of students, which are using instructional communication methods, namely the lecture method, individual practice, and the researcher also found the competition method used by teachers at the school.